A finite element level-set method for stress-based topology optimization of plate structures. (1st June 2022) - Nguyen, Son H.; Nguyen, Tan N.; Nguyen-Thoi, Trung
Highlights: Level-set method is applied for stress-based topology optimization of plate problems. Solving optimization problems with arbitrarily complex geometries and boundaries. A stabilized least-squares method is applied for solving level-set-based equations. The shape derivatives, adjoint method, and p -norm aggregation function are used. Abstract: In this paper, we present a stress-based topology optimization of plate structures by using a finite element level-set (LS) method. Since stress constraints are independent with LS-based design variables, the singularity phenomenon arising in topology optimization under stress constraints can be resolved without using any relaxation technique. The finite element method is used for solving LS-based equations of design variables and the state and adjoint equations of plate structures with arbitrary complex geometries and boundaries of the design domain. To obtain stable finite element solutions without any oscillation, both unsteady LS convection-diffusion equation and LS re-initialization convection-reaction equation are solved using a stabilized least-squares finite element method.